DESKRIPSI PEMBELAJARAN DARING MATA PELAJARAN MATEMATIKA PADA MASA PANDEMI COVID-19 - Karmelia Kristi Malonda; Ichdar Domu; Nicky Kurnia Tumalun (LPPM Universitas Bina Bangsa, 2023)
This study aims intended to describe the difficulties of online learning in mathematics for class IX students of SMP Negeri 9 Satap Langowan. This type of research is a qualitative descriptive study with a sample of class IX students with a total of students 22 and 1 teacher of mathematics in class IX. There are 3 data collection techniques used by researchers, namely: first, interviews with class IX mathematics teachers. Second, a questionnaire filled out by class IX students and thirdly documentation related to research images. Data analysis in this study is data reduction, data presentation, and drawing conclusions. Through observations made, students and teachers experienced difficulties when learning online, there are two kinds of difficulties that are found, namely the general difficulties experienced by schools and teachers is that there is no readiness from teachers when facing online learning because all learning from conventional changes to modern. These changes completely changed both the concept, the strategy method and even the assessment from the teacher to the students. There are also students who have difficulty understanding mathematics learning given by the teacher through the WhatsApp Group application